Perceived Stress and Coping Styles among Smoking and Non Smoking Undergraduates in Bangalore: An Empirical Study (Indian Journal of Psychology & Education, 2016)
Perceived stress and coping styles of adolescents can be a very imperative on initiation and sustenance of smoking. Through this study researcher explores the difference in perceived stress and coping style among sixty smoking and nonsmoking undergraduates. The participants answered a series of three questionnaires which studied their smoking behaviour, perceived stress and coping style. The outcomes of the study show a clear difference between the two groups the smoking undergraduates experience high level of stress when compared to non-smoking undergraduates. Non-smoking undergraduates had active emotional coping as their dominant coping style, whereas smoking undergraduates had passive problem solving coping style. The conclusions of this study show that adolescents need to be aware of the problems of the stage that they are going through and there should be some training in life skills and social skills so that they approach the problem situation in a more positive note which in turn would lead to a better healthy generation.